On the Supremacy and Privilege of ‘White-Skinned’ Subjects in Imperial Travel Writing - Moussaoui, Abdelghani (International Journal of Language and Literary Studies, 2024)
This paper offers an understanding of how Morocco, as a former French colony, is racially represented in Tom Gamble’s travel account Amazir: A Novel of Morocco (2010). It shows how the author into question, through racializing Morocco, has taken part in the shaping of colonialist discourse and the construction of ‘Otherness’ as a whole. The selected corpus deserves to be studied because it offers some theoretical perspectives that can be utilized as a guide to scrutinize other similar postcolonial travel narratives. After a postcolonial reading of Gamble’s narrative, it was inferred that Morocco is described as an ‘other space’ wherein the promises and limitations of the Western society are displaced, though not in a way this space is hermeneutically marked. The way Morocco has been delineated puts the West in the position of “creator”. This position of “creator” results in the necessity of dominating the different ‘Other’ and their ‘exotic’ space. The binarism of the ‘Self’ versus the ‘Other’ articulates the ‘racist’ discourse of imperial travel writing. It is not only a matter of mapping the ground for the so-called ‘civilizing mission’ but also a tool to enlarge the gap between the West and the Rest in cross-cultural encounters.